The Development of Physics Student Skills Test Using Basic Physics Measuring Instruments - Oka Melawati; Ngadimin Ngadimin; Soewarno Soewarno (Universitas Syiah Kuala, 2019)
Learning about laboratory equipment is often done. However, at the end of the learning that is often carried out tests is knowledge. While the skills possessed by students are rarely carried out tests, even though skills are part of the competencies that must be achieved. This can be caused by the unavailability of test kits that can be used to measure skills. Therefore in this study researchers conducted research on the development of physics student skills tests using basic physics measuring instruments in the Fkip Unsyiah Physics Education laboratory. This study aims to obtain a skill test device using a valid basic physics measurement tool for physics education study program students. The products produced are in the form of assessment instruments in the form of rubrics on a scale of 1-3. This study uses the development model Rowntree which consists of three stages, namely: 1) Planning; 2) Development; and 3) Evaluation. The results showed that the instrument validation obtained a percentage of 80% with a very feasible category. While the results of the average percentage of practical performance using calipers is 90.3%, micrometer 92.1%, voltmeter 81.5%, and ampermeter 81.6%. That is, the average percentage of student performance is categorized as very feasible.